Less is More? The ECtHR’s Judgment on the Voting Rights of National Minority Voters in Hungary - Horváth, Attila (The ECHR at 70: The Central European Narrative, 2025)
In 2011, Hungarian Parliament passed a new electoral law that – unlike the previous legislation – contained elements of positive discrimination in favour of the national minorities to promote their representation in Parliament and to enhance their political participation. After the 2014 parliamentary elections, the system of national minority voting was challenged before the European Court of Human Rights by two minority voters, claiming that the voting system constituted discriminatory interference with their voting rights (Bakirdzi and E.C. v. Hungary). The applicants relied on Article 3 of Protocol No. 1 (right to free elections) to the European Convention on Human Rights taken alone and in conjunction with Article 14 of the Convention (prohibition of discrimination). The Court found that the combination of the restrictions on the applicants’ voting rights, considering their total effect, constituted a violation of both of the articles of the Convention.The current study outlines the background of the case, paying special attention to the challenged legal framework and the outcome of the last three parliamentary elections, and then analyses the procedure before the Court. As the relevant statutory scheme has not yet been amended, the summary outlines some possible ways in which the Government could bring the domestic legal framework into line with theprinciples set out in the judgement.The judgement may be of interest for at least two reasons. On the one hand, the decision sheds light on the problems that lawmakers must face when elaborating the voting system of national minority voters. On the other hand, the judgement analysed here helps us to explore the meaning of ‘equal suffrage’, ‘free elections’ or ‘secrecy of vote’. According to some views, the Court has not yet carried out such an abstract examination of the legislation of the Member States ensuring the effective participation of national minorities in public life. Therefore, the judgment may also have an international impact.Keywords: national minorities, right to vote, equal suffrage, free expression of opinion of people, discrimination, Hungary